Estate planning basics : what you need to know about wills, trusts & avoiding probate - Clifford, Denis (Nolo, 2024)
"Get the need-to-know basics about wills, trusts, avoiding probate, and planning for incapacity with Estate Planning Basics. This book lays out your options in plain English, guiding you to the right estate plan for you and your family." --